Analysis of Evaluation Policies in the Philanthropic Sector. (June 2022) - Kinarsky, Alana R.; Christie, Christina A.
Since 2007, two taxonomies have been proposed to identify the components of evaluation practice that may be specified in an evaluation policy. Little is known, however, about how these taxonomies align with evaluation policies developed by philanthropic foundations. Through thematic analysis, this article first compares 12 foundation evaluation policies to the components of the two existing taxonomies. Based on this analysis, an updated taxonomy is proposed, with 11 components to inform evaluation policies in the philanthropic sector and beyond. The 12 foundation policies are then reexamined in relation to the new taxonomy to compare their length, breadth, and depth. This article concludes with implications for practice and suggestions for future research.